INFORMATION SYSTEM SALES OF INDOOR AND OUTDOOR ORNAMENTAL PLANTS-BASED ONLINE - Sutedi Sutedi (STMIK Pringsewu Lampung, 2017)
Ornamental plants have fairly high commercial value and much sought after by various circles. The prospect is in the business of ornamental plants can be said very brilliant and profitable. Where is in the business of ornamental plants can bring about advantages not the least. The business struggled with ornamental plants can have very favorable prospects for the long term. There are an awful lot of various kinds of ornamental plants that we can choose to use as ornaments to beautify residential home. The ornamental plants can be used as indoor ornamental plants placed in homes or can also be used as outdoor ornamental plants grown in the garden. Ornamental plants while more popular community-wide information system for ornamental plant however is currently designed specifically and not many people who know the information on price and specs or type of indoor and outdoor ornamental plants so that the need for sales information system of indoor and outdoor ornamental plants-based online. With the sales information system of Indoor and Outdoor ornamental plants-based online is expected to facilitate the customers, business processes that occur in the company's units, unit – units that exist within the system a functioning production units as the unit working on/produce ornamental plants. With the utilization of the system marketing media, promoting, finding new customers, the sales process, recapitulation payment of ornamental plants, control the conditions of stock products, development and delivery of products to customers including convincing the product gets to the customer